Complications of total temporomandibular joint replacement: a systematic review and meta-analysis - Peres Lima, F. G.G.; Rios, L. G.C.; Bianchi, J.; Gonçalves, J. R. [UNESP]; Paranhos, L. R.; Vieira, W. A.; Zanetta-Barbosa, D. (Elsevier, 2023)
The aim of this systematic review was to determine the most prevalent complications resulting from total temporomandibular joint (TMJ) replacement. An electronic search was performed using the Embase, LILACS, MEDLINE (via PubMed), SciELO, Scopus, and Web of Science databases up to June 2022. Prospective and retrospective clinical studies on patients who underwent TMJ replacement were included. Two reviewers performed the study selection, data extraction, and individual risk of bias assessment using the Joanna Briggs Institute Critical Appraisal Tools. The pooled prevalence of each complication was calculated through a proportion meta-analysis using the random-effects model. Twenty-eight studies met the eligibility criteria and were included in the review. All of the eligible studies had a low risk of bias. The results of the meta-analysis revealed that the most prevalent complication was paresis or paralysis of the facial nerve branches (7.8%; 95% confidence interval (CI) 2.6–15.1%, I2 = 94.5%), followed by sensory alterations (1.8%; 95% CI 0.6–4.9%, I2 = 88.8%), heterotopic bone formation (1.0%; 95% CI 0.1–2.5%, I2 = 75.8%), and infection (0.7%; 95% CI 0.1–1.6%, I2 = 22.7%). In conclusion, TMJ replacement has a low prevalence of complications, and most of them can be managed successfully.
Keywords: Intraoperative complications; Joint prosthesis; Mandibular prosthesis; Postoperative complications; Temporomandibular joint disorders